Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1348/014466502760379136
|View full text |Cite
|
Sign up to set email alerts
|

Which schizotypal dimensions abolish latent inhibition?

Abstract: Our results support the proposition that the cognitive processes underlying the mediation of LI are related to the genesis of unusual experiences in schizotypy and, by extension, the positive symptoms of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 40 publications
6
40
2
Order By: Relevance
“…However, contrary to the hypothesis and the findings of Granger et al [31] there was no association between the OS scores and the O-LIFE subscales, specifically UnExp, as was found in the Granger et al [31] study or CogDis which has been linked to attentional difficulties as measured in LI and KB [13,29,30]. One explanation is that the tasks used here were different from that used to show OS in Granger et al [31].…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…However, contrary to the hypothesis and the findings of Granger et al [31] there was no association between the OS scores and the O-LIFE subscales, specifically UnExp, as was found in the Granger et al [31] study or CogDis which has been linked to attentional difficulties as measured in LI and KB [13,29,30]. One explanation is that the tasks used here were different from that used to show OS in Granger et al [31].…”
Section: Discussioncontrasting
confidence: 79%
“…Such methodological differences may account for the relationship between OS and O-LIFE scores shown in Granger et al [31]. In any event, the results of the present study may be taken to suggest that the relationship between O-LIFE scores and OS is less compelling than that demonstrated for LI and KB [13,[28][29][30]. Consistent with this interpretation, there is evidence from animal studies that LI and KB are modulated by different neural substrates to OS [19][20][21].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The Oxford-Liverpool Inventory for Feelings and Experiences consists of 159 items selected on the basis of factor-analytic studies of older scales assessing psychotic-like features in the general population (Mason, Claridge, & Jackson, 1995). Contributing to the experimental validity of this inventory, various studies have confirmed that high schizotypy scorers, as identified by the O-LIFE sub-scales, demonstrate cognitive deficits similar to those seen in schizophrenic patients (Burch, Steel, & Hemsley, 1998;Goodarzi, Wykes, & Hemsley, 2000;Gray, Fernandez, Williams, Ruddle, & Snowden, 2002;Tsakanikos & Reed, 2003). More specifically, it assesses the following dimensions:…”
Section: Schizotypy Measuresmentioning
confidence: 99%